gAChR antibodies in children and adolescents with acquired autoimmune dysautonomia in Japan - Yamakawa, Makoto (Ann Clin Transl Neurol, 2021)
OBJECTIVE: Patients with acquired autonomic dysfunction may have antibodies specific to the ganglionic nicotinic acetylcholine receptor (gAChR). However, the clinical features of children and adolescents with acquired autonomic dysfunction (AAD) remain unclear. This study aimed to determine the clinical features of pediatric patients with acquired autonomic dysfunction. METHODS: This study retrospectively examined a series of patients of AAD with serum gAChR antibodies who were referred to our laboratory for antibody testing between January 2012 and April 2019. The study included 200 patients (<20 years, 20 cases; ≥20 years, 175 cases) with clinical features of AAD. RESULTS: Upon comparing pediatric and adult patients, we found that antecedent infection and autonomic symptoms at onset with gastrointestinal symptoms occurred more frequently in children with AAD. We confirmed that four children (20.0%) met the diagnostic criteria for postural orthostatic tachycardia syndrome (POTS). A significantly higher number of children than adults had POTS (P = 0.002). In addition, upper GI dysfunction was more prevalent in children than in adults (P = 0.042). In particular, nausea and vomiting occurred in 60.0% of children with AAD and in 21.1% of adults (P < 0.001). The frequency of paralytic ileus was significantly higher in children with AAD (20.0%) relative to adults (6.3%) (P = 0.030). Regarding extra‐autonomic manifestations, encephalopathy was more frequent in children (15.0%) than in adults (1.1%) (P < 0.001). INTERPRETATION: Pediatric AAD patients have their own clinical characteristics, and these features may be unique to children and adolescents.